Analysis of Variations in The Use of Numeral Classifier to Count Mode of Transportation in Japanese - Wahyuni, Sri (Makassar State University, 2024)
Abstract. This study aimed to describe the numeral classifier for counting the mode of transportation in Japanese and explain its use. Data collection was carried out using the observation method with basic tapping techniques. Data analysis was conducted using the intralingual matching method, with three basic techniques: the comparative and equalize technique, the comparative and differentiate technique, and the comparative and equalize the main thing. The research results showed variations in the Japanese numeral classifier used to count land, water, and air transportation. The most significant variation was found in counting water transportation, which were 13 numeral classifiers found: seki, sō, tei, hai, kan, sen, ha/yō, hon, hen, han/ho, mai, fusa, and toko/shō. In contrast, the slightest variation was found in counting air transportation, with four variations of the numeral classifier: ki, dai, bin, and seki. To count land transportation, 11 numeral classifiers were found, namely chō/tei, ryō, dai, tōtachi, rin, jō, hon, ressha, kisha, hansei, and bin. Although various numeral classifiers were used for each type of transportation, the same numeral classifiers could be used to count the two different transportation types. The hon numeral classifier was a numeral classifier that could be used to count both land and water types of transportation. Of the four numeral classifiers used to count air transportation, three could also be used to count land and water transportation. Apart from being used to count transportation in the air, the numeral classifiers dai and bin were also used to count the transportation type on land. In contrast, the numeral classifier seki, used to count air transportation, was also used to count water transportation. On the other hand, some numeral classifiers could also be used to count various types of transportation depending on the object's point of view.Keywords: air transportation, land transportation, Japanese, numeral classifier, water transportation